Promising new applications of Castanea sativa shell: nutritional composition, antioxidant activity, amino acids and vitamin E profile. Issue 8 (5th August 2015) - Rodrigues, Francisca; Santos, Joana; Pimentel, Filipa B.; Braga, Nair; Palmeira-de-Oliveira, Ana; Oliveira, M. Beatriz P. P.
<x xml:space="preserve">Abstract</x> The present study was aimed to assess the macronutrient composition and the amino acid and vitamin E profiles of Castanea sativa shell from different production regions of Portugal (Minho, Trás-os-Montes and Beira-Alta).